The Impact of Working Capital Management, Cash Flow Volatility, and Leverage on Financial Sustainability - Sri Mulyono; Zamhuri Rachman; Aziz Septiatin; Hadi Peristiwo (Malaqbi Publisher, 2026)
This study aims to examine the impact of working capital management, cash flow volatility, and leverage on financial sustainability. In an increasingly uncertain and competitive business environment, financial sustainability has become a critical objective for firms seeking long-term stability and growth. This research adopts a quantitative approach using panel data collected from companies listed on the Indonesia Stock Exchange (IDX) over the period 2020–2024. The sample was selected using purposive sampling, resulting in firm-year observations that meet the research criteria. Data were analyzed using panel data regression with the Fixed Effect Model, following the results of model selection tests. The findings reveal that working capital management has a positive and significant effect on financial sustainability, indicating that efficient management of short-term assets and liabilities enhances liquidity and supports long-term financial stability. In contrast, cash flow volatility has a negative and significant effect, suggesting that fluctuations in cash flows increase financial uncertainty and weaken a firm’s ability to sustain operations. Similarly, leverage is found to have a negative and significant impact on financial sustainability, implying that excessive reliance on debt increases financial risk and reduces resilience. Additionally, control variables such as firm size, profitability, and growth are shown to positively influence financial sustainability. Overall, this study highlights the importance of effective financial management practices in achieving financial sustainability. Firms are encouraged to optimize working capital efficiency, stabilize cash flows, and maintain prudent leverage levels to enhance long-term performance and resilience. This research contributes to the literature by providing an integrated analysis of key financial determinants of sustainability and offers practical implications for managers and policymakers in improving financial decision-making.